Sengketa Jual Beli Tanah Yang Dilakukan dengan Akta Jual Beli Fiktif (Studi Putusan Pengadilan Negeri Klaten No.50/PDT.G/2012/PN.Klt) - Anggraini, Eviana Putri; , Shalman Al Farizi,S.H.,M.Kn (2017)
This study aims to determine the consideration of the judge in determining the verdict disputed land purchase made by the deed of sale of fictitious and to determine the legal effect of the decision No. 50 / PDT.G / 2012 / PN.Klt. This study uses normative legal approach. Data collection techniques in this research is the study of literature and analyzed by qualitative data analysis, analyze the court decision related to land purchase made by the deed of sale of fictitious. The results of this study indicate that (1) the legal considerations Klaten District Court No. 50 / PDT.G / 2012 / PN.Klt mastery certificate by the Defendants unlawfully (2) buying and selling land that turned out to be done in fictitious.